2017
DOI: 10.3892/ol.2017.7585
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of decannulation, oral intake recovery, overall survival and lung metastasis following oral malignant tumor resection and reconstruction

Abstract: Abstract. The present study investigated whether tongue base and mandibular bone defects were associated with the rate of decannulation and oral intake recovery, and survival time, including overall and lung metastasis-free survival time, in patients that underwent oral malignant tumor (OMT) resection with reconstruction. A total of 105 patients that underwent OMT resection with laryngeal preservation and reconstruction were recruited. The extent of defects was classified according to Urken's classification. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Overall, the most important variables influencing deglutition were adjuvant treatment, age, gender, oropharyngeal resection, and type of free flap employed, as previously reported in literature 19–23 . Performing functional evaluation at 6 and 12 months showed that it is reasonable to expect some improvements up to 1 year after surgery, as also confirmed by other studies 24–27 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Overall, the most important variables influencing deglutition were adjuvant treatment, age, gender, oropharyngeal resection, and type of free flap employed, as previously reported in literature 19–23 . Performing functional evaluation at 6 and 12 months showed that it is reasonable to expect some improvements up to 1 year after surgery, as also confirmed by other studies 24–27 .…”
Section: Discussionsupporting
confidence: 81%
“…Overall, the most important variables influencing deglutition were adjuvant treatment, age, gender, oropharyngeal resection, and type of free flap employed, as previously reported in literature. [19][20][21][22][23] Performing functional evaluation at 6 and 12 months showed that it is reasonable to expect some improvements up to 1 year after surgery, as also confirmed by other studies. [24][25][26][27] It is interesting to note how at 1 year after treatment patients' subjective perception of swallowing is generally reported as good/satisfactory in more than 50% of cases using both the EORTC and UWQOL questionnaires.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…At present, lung tumor metastasis is the most difficult treatment barrier in cancer therapy (14)(15)(16). Therefore, obtaining an early diagnosis for human tumors is crucial for the effective treatment of human lung cancer (17).…”
Section: Introductionmentioning
confidence: 99%